Missed Opportunities for HIV Testing and Late-Stage Diagnosis among HIV-Infected Patients in Uganda - Wanyenze, Rhoda K.; Kamya, Moses R.; Fatch, Robin; Mayanja-Kizza, Harriet; Baveewo, Steven; Sawires, Sharif; Bangsberg, David R.; Coates, Thomas; Hahn, Judith A. (PLoS ONE, 2011)
Late diagnosis of HIV infection is a major challenge to the scale-up of HIV prevention and treatment. In 2005 Uganda adopted provider-initiated HIV testing in the health care setting to ensure earlier HIV diagnosis and linkage to care. We provided HIV testing to patients at Mulago hospital in Uganda, and performed CD4 tests to assess disease stage at diagnosis. Methods: Patients who had never tested for HIV or tested negative over one year prior to recruitment were enrolled between May 2008 and March 2010. Participants who tested HIV positive had a blood draw for CD4. Late HIV diagnosis was defined as CD4#250 cells/mm. Predictors of late HIV diagnosis were analyzed using multi-variable logistic regression. Results: Of 1966 participants, 616 (31.3%) were HIV infected; 47.6% of these (291) had CD4 counts #250. Overall, 66.7% (408) of the HIV infected participants had never received care in a medical clinic. Receiving care in a non-medical setting (home, traditional healer and drug stores) had a threefold increase in the odds of late diagnosis (OR = 3.2; 95%CI: 2.1–4.9) compared to receiving no health care. Conclusions: Late HIV diagnosis remains prevalent five years after introducing provider-initiated HIV testing in Uganda. Many individuals diagnosed with advanced HIV did not have prior exposure to medical clinics and could not have benefitted from the expansion of provider initiated HIV testing within health facilities. In addition to provider-initiated testing, approaches that reach individuals using non-hospital based encounters should be expanded to ensure early HIV diagnosis.
Keywords: HIV Testing; Late-Stage Diagnosis; HIV-Infected Patients; Uganda